Colonies humaines et cosmos - Barthomeuf, Perrine (Journal international de bioéthique et d'éthique des sciences, 2019)
We have come far from the days when space activities were the monopoly of States. Henceforth, private actors, from the tech world, possess significant financial means which they intend to mobilise in order to exploit the resources of outer space commercially and, eventually, to inhabit outer space. As a result, the principle of non-appropriation of celestial bodies is seen by some as an impediment to the development of the exploitation of space. Is it really possible to envisage a human community inhabiting outer space without claiming exclusive rights on the surface of celestial bodies? Can the resources extracted from celestial bodies be appropriated and if so what legal regime could manage the said resources? This article attempts to answer these questions with a double approach focussing on the ownership of celestial resources and the ownership of celestial bodies. The recognition since the Obama Act that celestial resources can be appropriated imposes a model of management of the said resources in the interests of the whole of mankind. Likewise, without undermining the fundamental principle of non-appropriation, States should establish themselves as the managers and guarantors of the use of celestial bodies in that they constitute the common heritage of Earth’s community.